Peanut digestome: Identification of digestion resistant IgE binding peptides. (September 2017) - Di Stasio, Luigia; Picariello, Gianluca; Mongiello, Mariantonietta; Nocerino, Rita; Berni Canani, Roberto; Bavaro, Simona; Monaci, Linda; Ferranti, Pasquale; Mamone, Gianfranco
Abstract: Stability to proteolytic degradation in the digestive tract is considered a general feature shared by most food allergens. Current digestibility models exclusively utilize purified allergen proteins, neglecting the relevant effects of matrix that occur for foodstuff systems. In the present study, we investigated digestion stability of the major peanut allergens directly in the natural matrix using an in vitro static model that simulates the gastrointestinal digestion including the oral, gastric, duodenal and intestinal (brush border membrane enzymes) phases. Immunogenicity was evaluated by Western Blot using N=8 pooled sera of peanut allergic pediatric subjects. Immunoreactive, large-sized and fragments of Ara h 2, Ara h 6 and Ara h 3 survived hydrolysis as assessed by SDS-PAGE. Smaller resistant peptides mainly arising from Ara h 3 and also Ara h 1 were detected and further identified by LC-high resolution-MS/MS. RP-HPLC purification followed by dot-blot analysis and MS/MS-based identification demonstrated that stable IgE-binding peptides derived from Ara h 3. These results provide a more realistic picture of the potentially allergenic determinants of peanuts that survived the human digestion, taking into account the role of the food matrix, which may significantly affect gastrointestinal breakdown of peanut allergens. Graphical abstract: Highlights: A realistic picture of the potentially allergenic peanuts is provided. Large fragments of Ara h 3, survive to in vitro gastrointestinal digestion. Ara h 3 IgE binding epitopes are released during gastrointestinal digestion. Ara h 1 is completely degraded following in vitro gastrointestinal digestion. Peanut matrix slows the gastrointestinal digestion process of allergen proteins.